Strengthening Inclusive Education in a Colombian Institution of Higher Education - Yeison Guerrero (JIE, 2024)
This research aimed to explore the actions for strengthening of attention to diversity in a higher education institution. The study was designed on the descriptive type of methodology for prospective multivariate analysis. The instrument used was the Índice de Inclusión para la Educación Superior [Index for Inclusion in Higher Education]. The research was conducted in five stages: At stage 1, representatives of the different bodies in the institution were selected and trained. At stage 2, an awareness and training process was carried out with the entire community. At stage 3, a probability sampling was performed and the instrument was applied. At stage 4, through a Multiple Correspondence Analysis and a Multiple Factor Analysis, the indexes by factors of accreditation, institution, and population group were constructed. Finally, the actions for the strengthening of inclusive education were prioritized. It was found that Inclusive Education demands efforts for its development, especially in organization, management, and administration, in academic support resources and physical infrastructure, and in financial resources. Additionally, it was found that professors are the most critical group in this regard. Based on the results, priority actions are proposed to be integrated into the institutional development plan.